A woman of letters : an examination of the character of Margaret Paston through a selective reading of Paston letters and papers of the fifteenth century - Purvis, Rosemary (Department of English Language and Literature, 2016)
The study examines the character of Margaret Paston through a selective reading of Paston Letters and Papers of the fifteenth century. Consideration is given to the problems posed by the letter form, to the identification of an authentic "voice" in the letters of a woman who was probably unable to write, and to the constraints of an incomplete historical record. Margaret is viewed by means of her own words and her relationships with her immediate and extended family, and in the light of the social and political circumstances of the time. It is concluded that by examining Margaret in this way, there is sufficient material in the epistolary record to make an assessment of her character.